2014
DOI: 10.1177/0004867414533834
|View full text |Cite
|
Sign up to set email alerts
|

Are child and adolescent mental health problems increasing in the 21st century? A systematic review

Abstract: These findings suggest that recent cohorts of adolescent girls are experiencing increases in internalizing symptoms compared to previous cohorts. Approaches for prevention and early intervention should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
518
10
27

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(603 citation statements)
references
References 54 publications
48
518
10
27
Order By: Relevance
“…[18][19][20] These individual vulnerabilities can make peer relations stressful, particularly among female adolescents who are more susceptible to interpersonal stress compared to males. [21][22][23][24] The empirical evidence is consistent with the theoretical arguments for expecting CV to exert a negative influence on adolescent mental health. A recent meta-analysis investigating the association between CV and adolescent psychological problems suggests a small-to-moderate association between CV and levels of depression (r = 0.24; k = 30 studies), anxiety (r = 0.24; k = 14 studies), and drug and alcohol use (r = 0.15; k = 6 studies).…”
Section: Impact Of Cyberbullying Victimization On Mental Health and Ssupporting
confidence: 72%
“…[18][19][20] These individual vulnerabilities can make peer relations stressful, particularly among female adolescents who are more susceptible to interpersonal stress compared to males. [21][22][23][24] The empirical evidence is consistent with the theoretical arguments for expecting CV to exert a negative influence on adolescent mental health. A recent meta-analysis investigating the association between CV and adolescent psychological problems suggests a small-to-moderate association between CV and levels of depression (r = 0.24; k = 30 studies), anxiety (r = 0.24; k = 14 studies), and drug and alcohol use (r = 0.15; k = 6 studies).…”
Section: Impact Of Cyberbullying Victimization On Mental Health and Ssupporting
confidence: 72%
“…The repeatedly described increase in the prevalence of particular mental health problems among youth over the last decades (Bor et al, 2014;Collishaw et al, 2004;Collishaw et al, 2010) might be at least partly attributable to an increased willingness of young people to talk about mental health problems.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown an increasing prevalence of some mental health problems in both youth (Bor et al, 2014;Collishaw et al, 2004;Collishaw et al, 2010) and adult (Jorm and Butterworth, 2006;Mojtabai, 2011;Reavley et al, 2011) populations in recent decades. This change might reflect an actual worsening of the population's mental health (Collishaw et al, 2004;Collishaw et al, 2010) or may be due to an increased willingness to disclose diagnosed disorders or symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Leaving home at an early age entails different kinds of transitions, and moving away from home at this age, while simultaneously attending a new school, seems to affect adolescents’ well-being, creating the risk of dropping out of school and/or potential mental health problems (Markussen, 2005, 2011). An increase in mental health problems in adolescents, especially among girls, during the last 20 years has been identified (Bor, Dean, Najman, & Hayatbakhsh, 2014; Collishaw, 2015; Von Soest & Wichstrøm, 2014). Likewise, a Norwegian study found that students living in lodgings during senior high school were particularly vulnerable to stress and internalizing problems compared to students living with their parents (Wannebo & Wichstrøm, 2010).…”
Section: Introductionmentioning
confidence: 99%